Gradenigo's syndrome in a four-year-old patient: a rare diagnosis in the modern antibiotic era. Issue 6 (28th May 2019) - Rossi, N; Swonke, M L; Reichert, L; Young, D
Abstract: Objective: This study gives details of a rare case of petrous apicitis that presented as Gradenigo's syndrome and was managed surgically. Method: This study presents a case report and review of the literature. Results: A four-year-old female was admitted for failure to thrive following recent sinusitis. Physical examination was positive for right sided facial pain, photophobia and right abducens nerve palsy. Subsequent magnetic resonance imaging revealed a 1.3 × 1.7 × 1.4 cm abscess encompassing the right Meckel's cave. A computed tomography scan showed petrous apicitis and otomastoiditis, confirming Gradenigo's syndrome. The patient was taken to the operating theatre for right intact canal wall mastoidectomy with myringotomy and tube placement. She was discharged on six weeks of ceftriaxone administered by a peripherally inserted central catheter line. At a two-week post-operative visit, she showed notable improvement in neuropathic symptoms. Conclusion: This study presents a rare case of petrous apicitis managed surgically without the need for a craniotomy or transcochlear procedure.